(3GdQcf GdeYfhj aj GdeNGdaGJ(B/s - (3YeQ GdSYjO QeVGfs; (3eMehO eMehO eUWais; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 1959)
(3jJfGhd GdHMK OQGSI ehVhY GdQcf GdeYfhj ddeNGdaGJ hjHOC HHMK GdWHjYI GdbGfhfjI ddeNGdaGJ hjfGbT eNJda GdfXQjGJ GdJj JMGhd Gf Jbje GdJaQbI Hjf GdeNGdaGJ hHjf ZjQgG ef GdLQGFe Ydj CSGS eSJeO ef GdWHjYI GdOGNdjI ddaYd Gdechf ddLQjeI Ke jHjf GdHMK ehba GdbGfhf GdhVYj ef gPg GdfXQjGJ Ke GfJbd GdHMK HYO Pdc Gdj JMOjO GdQcf GdeYfhj aj GdLQjeI HUaI YGeI hgh eG jSej HYfUQ GdEKe jdj Pdc YQV debheGJg hUhQg hgj JTed GdbUO hGdNWC Ke jJfGhd GdHMK OQGSI GdQcf GdeYfhj aj GdeNGdaGJ aj GdbGfhf GdaQfSj haj GdbGfhf GdEjWGdj hCNjQG aj GdbGfhf GdeUQj ajLeY Gdabg GdaQfSj aj eUQ Ydj VQhQI Qcf eYfhj aj GdeNGdaGJ hJPgH GdfXQjI GdJbdjOjI aj aQfSG Gdj Gf GdeNGdaGJ LQGFe eGOjI HMJg jYGbH ajgG GdbGfhf Ydj GdaYd GdeGOj Gdechf dgG hMOI(B0 (3CeG GdbGfhf GdGjWGdj agh YcS GdbGfhfjf GdaQfSj hGdeUQj hjJVef fUG UQjMG HNUhU GdQcf GdeYfhj aj GdeNGdaGJ(B0 (3aj fgGjI GdHMK jJfGhd GdHGMK GdfXQjI GdebJQMI HNUhU GdQcf GdeYfhj aj GdeNGdaGJ eY YQ V dGge JWHjbGJgG hjfJgj GdHGMK Cdj CKHGJ ehGfY GdeSFhdjI aj GdeNGdaGJ aEPG cGfJ GdfjGHI GdYGeI djS YdjgG GHJOGA GbGeI GdOdjd Ydj GdQcf GeYfhj aj gPg GdLQGFe aEfg jchf HGdYcS Ydj GdeJge Cf jKHJ JNda gPG GdQcf(B.s
Addresses the Study of Multi mental element of the offense and starts examining the legal nature of the irregularities and discusses the various theories that try to establish a distinction between the offenses and the other crimes on the basis derived from the inner nature of the act component of the crime, and research shows the position of the positive law of these theories and then go search then to determine the mental element of the crime in general which is called the element of sin, followed by the presentation of its components and manifestations which include intent and error, and then addresses the Study of the mental element in the irregularities in the French law and Italian law, and finally in the Egyptian law combines jurisprudence French in Egypt on the need for a mental element in irregularities and go the traditional theory in France that the irregularities crimes purely material punishable where the law on the physical act component of her unit 0 The Italian law is unlike laws French, Egyptian, and includes explicit provision concerning the mental element in irregularities 0 at the end of the research deals with researcher theory proposed on the mental element in irregularities with Presentation Z of the most important applications and ends with the researcher to demonstrate responsibility in the contraceptives irregularities If the public prosecutor does not have starting to find evidence corner Amanue in these crimes, it would be contrary to the accused to prove this corner retardation.
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFj, (B1959s
(3jTJed Ydi EQLGYGJ HjHdjhLQGajI(B: 217-222 (3UaMIs
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdQcf GdeYfhj aj GdLQjeIs; (3GdQcf GdeYfhj aj GdeNGdaGJs; (3GdWHjYI GdbGfhfjI ddeNGdaGJs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs